2012
DOI: 10.4103/0972-124x.94598
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in HbA1c levels following non-surgical periodontal therapy in type-2 diabetic patients with chronic generalized periodontitis: A periodontist′s role

Abstract: Background:Aim of the study was to compare the response to non-surgical periodontal therapy between patients with and without type-2 diabetes from clinical and metabolic stand point.Materials and Methods:A comparative clinical study was performed between type 2 diabetics and non-diabetics with moderate generalized chronic periodontitis. The study period was six months. Conventional periodontal scaling and root planing were performed, and the response to this treatment was compared between the groups at three a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
5
1
4
Order By: Relevance
“…However the mean change in HbA1c seems to be larger than the one found in similar studies in diabetic patients from other regions and especially in developed countries [ 19 21 , 30 , 34 ]. This can be related to study population and periodontal therapy used.…”
Section: Discussioncontrasting
confidence: 65%
“…However the mean change in HbA1c seems to be larger than the one found in similar studies in diabetic patients from other regions and especially in developed countries [ 19 21 , 30 , 34 ]. This can be related to study population and periodontal therapy used.…”
Section: Discussioncontrasting
confidence: 65%
“…Nos estudos de Da Cruz et al 17 foram melhorados o índice de placa em todos os tempos para diabéticos e não diabéticos após 3 meses, assim como o índice de sangramento gengival. Resultados semelhantes com respeito a essas variáveis foram encontradospor outros autores para o índice de placa 8,12,13,16,18,19,25 e índice gengival. 8,13,16,18,19 A redução significativa desses parâmetros após a terapia confirma a eficácia do controle de higiene oral e redução da inflamação gengival.…”
Section: Discussionunclassified
“…O nível clínico de inserção também reduziu após o tratamento nãocirúrgico nos estudos realizados por Navarro-Sanchez, Faria-Almeida e Bascones-Martinez. 20 No entanto, Da Cruz et al 17 não encontrou diferenças estatisticamente significativas para ambos os grupos, assim como outros autores 8,13,18,19 quando comparados diabéticos com não diabéticos após o tratamento periodontal.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Many studies clearly reported that the estimation of HbA1c can be an important and reliable parameter to evaluate the effective periodontal treatment on the level of glycemic control. [ 20 ] The purpose of this study is to investigate the effects clinical and metabolic effects of a xanthan-based CHX (Xan-CHX) gel used as an adjunct to SRP in the treatment of Type 2 diabetic patients with chronic periodontitis.…”
Section: Introductionmentioning
confidence: 99%